THE CONCEPTUAL USE OF ANIMAL METAPHORS IN THE REPRESENTATION OF HUMANS IN ENGLISH AND UZBEK PROVERBS - Normuradova, Gulnora (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
Proverbs hold significant cultural value as succinct expressions of collective wisdom, reflecting the attitudes, beliefs, and values of a society. Embedded within these short, memorable sayings are insights into cultural norms, social hierarchies, and the human condition. Proverbs serve as a window into the cultural psyche, offering glimpses into societal perceptions of morality, gender roles, and interpersonal relationships. Animal metaphors are a common feature of proverbs across cultures, serving as powerful symbolic representations of human qualities, behaviors, and characteristics. Animals embody a rich array of cultural meanings and associations, making them potent vehicles for conveying complex ideas and cultural values. In proverbs, animal metaphors are employed to illustrate virtues, vices, and universal truths about human nature, providing vivid imagery that resonates with audiences. The purpose of this article is to undertake a comparative analysis of the conceptual use of animal metaphors in English and Uzbek proverbs to represent humans. By examining the underlying conceptual frameworks and cognitive associations embedded within these metaphors, this study aims to elucidate how animal imagery is employed to convey cultural perceptions of human behavior, identity, and social dynamics. Through this analysis, we seek to deepen our understanding of the cultural significance of animal metaphors in proverbs and their role in shaping cultural attitudes and beliefs about humanity.
Keywords: conceptual metaphors; humans; animals; source domain; target domain